The Hajar Aswad Jockey Phenomenon: Ethical Analysis and Implications for Pilgrim Management - Nafiroh, Nur Hidayatun; Rozaq, Abdul (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2025)
The phenomenon of Hajar Aswad jockeys, emerging from extreme overcrowding in the Grand Mosque, has triggered multidimensional polemics ranging from physical safety risks and social ethical dilemmas to disruptions in pilgrim management governance. This study aims to examine the Hajar Aswad jockey phenomenon in depth from the perspective of Islamic ethics and its implications for pilgrim management. This research employs a descriptive qualitative approach with a phenomenological method. Data were obtained through in-depth interviews with pilgrims, mutawwifs, and travel organizers, documentation observation, and literature study. Data analysis was conducted using the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. The results indicate that although the practice is perceived as facilitating worship for some pilgrims, it potentially poses safety risks, disorder, and degradation of moral values in worship. From an Islamic ethics perspective, this practice contradicts maqashid al-shari’ah principles, particularly hifz al-nafs (preservation of life) and hifz al-din (preservation of religion). Other implications include the need for pilgrim education, mutawwif accompaniment, and strengthening regulations to ensure safe, ethical practices that uphold the spiritual values of Hajj and Umrah. Fenomena joki Hajar Aswad yang muncul akibat kepadatan ekstrem di Masjidil Haram telah memicu polemik multidimensi, mulai dari risiko keselamatan fisik dan dilema etika sosial hingga gangguan terhadap tata kelola ketertiban jamaah. Penelitian ini bertujuan untuk mengkaji fenomena joki Hajar Aswad secara mendalam dari perspektif etika Islam serta implikasinya terhadap manajemen jamaah. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode fenomenologi. Data diperoleh melalui wawancara mendalam dengan jamaah, mutawwif, dan penyelenggara perjalanan ibadah, observasi dokumentasi, serta studi literatur. Analisis data dilakukan menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa meskipun praktik joki dianggap mempermudah ibadah bagi sebagian jamaah, praktik ini berpotensi menimbulkan risiko keselamatan, ketidaktertiban, dan penurunan nilai moral ibadah. Dari perspektif etika Islam, praktik ini bertentangan dengan prinsip maqashid al-shari’ah, khususnya hifz al-nafs (menjaga jiwa) dan hifz al-din (menjaga kesucian ibadah). Implikasi lain termasuk perlunya edukasi jamaah, pendampingan mutawwif, serta penguatan regulasi dan sosialisasi agar praktik joki berlangsung aman, etis, dan tetap memperhatikan nilai spiritual ibadah haji dan umrah.